Comprehensively mapping political science methods: an instructors' survey. Issue 2 (4th March 2017) - Blanchard, Philippe; Rihoux, Benoît; Álamos-Concha, Priscilla
Abstract: A map provides a unique view over the complex relationships of competition and complementarity between methods. It goes beyond the usual approaches to methods, namely monographic, mixed, encyclopaedic and classificatory. A diverse set of 50 social and political science methods instructors were surveyed about their specialty along 17 dimensions that are regarded as contrasting by the methodology literature. Correspondence analysis and cluster analysis were used to reveal response profiles and proximities between courses. Results show that the 'qualitative/quantitative' divide appears structuring, but not as much as is often conceived. Quantitative-oriented courses form a rather cohesive cluster whereas qualitative courses display high variability regarding empirical material, scales of observation, techniques and epistemologies. The resulting global picture accounts for more dimensions of the quickly expanding space of methods than usual typologies of methods do. We hope it will stimulate new methodological combinations and new ways of teaching methods.